2014
DOI: 10.1155/2014/878450
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs: Promising New Antiangiogenic Targets in Cancer

Abstract: MicroRNAs are one class of small, endogenous, non-coding RNAs that are approximately 22 nucleotides in length; they are very numerous, have been phylogenetically conserved, and involved in biological processes such as development, differentiation, cell proliferation, and apoptosis. MicroRNAs contribute to modulating the expression levels of specific proteins based on sequence complementarity with their target mRNA molecules and so they play a key role in both health and disease. Angiogenesis is the process of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 144 publications
0
41
0
Order By: Relevance
“…We will focus on mi-RNAs, short (18-25 base) oligomers encoded in the genome that repress translation of target genes by complexing with mRNAs, leading to inhibition of translation and/or increased mRNA degradation [74], as this subgroup of noncoding RNAs has been significantly studied in stromal cells. A large number of miRNAs have been identified in the human genome and each species of miRNA may have multiple mRNA targets [75]. Many individual miRNA species have been shown to play roles in the regulation of stromal cells of the tumor microenvironment and this subject has recently been reviewed [76][77][78][79].…”
Section: Intra-and Intercellular Regulation Of Stromal Cells By Mirnasmentioning
confidence: 99%
“…We will focus on mi-RNAs, short (18-25 base) oligomers encoded in the genome that repress translation of target genes by complexing with mRNAs, leading to inhibition of translation and/or increased mRNA degradation [74], as this subgroup of noncoding RNAs has been significantly studied in stromal cells. A large number of miRNAs have been identified in the human genome and each species of miRNA may have multiple mRNA targets [75]. Many individual miRNA species have been shown to play roles in the regulation of stromal cells of the tumor microenvironment and this subject has recently been reviewed [76][77][78][79].…”
Section: Intra-and Intercellular Regulation Of Stromal Cells By Mirnasmentioning
confidence: 99%
“…MiRNAs are closely associated with tumor occurrence and development. Some miRNAs can promote tumor proliferation and metastasis, whereas others inhibit tumorigenesis (Gallach et al, 2014;Lindner et al, 2015). Previous research showed that miRNAs are abnormally expressed in osteosarcoma, and may function as oncogenes or tumor suppressors.…”
Section: Introductionmentioning
confidence: 99%
“…For in-depth discussions, we refer the reader to dedicated reviews [1619]. miRNAs are highly expressed in EC, and they can regulate most aspects of vascular development and angiogenesis.…”
Section: Mirnas In Tumor Angiogenesismentioning
confidence: 99%